Molecular characterisation of aflatoxigenic and non-aflatoxigenic strains of Aspergillus section Flavi isolated from imported peanuts along the supply chain in Malaysia - Mahror, Norlia; Selamat, Jinap; Mahmud @ Ab Rashid, Nor Khaizura; Radu, Son; Chin, Cheow Keat; Samsudin, Nik Iskandar Putra; Abdul Halim, Farawahida (MDPI, 2019)
Peanuts are widely consumed in many local dishes in southeast Asian countries, especially in Malaysia which is one of the major peanut-importing countries in this region. Therefore, Aspergillus spp. and aflatoxin contamination in peanuts during storage are becoming major concerns due to the tropical weather in this region that favours the growth of aflatoxigenic fungi. The present study thus aimed to molecularly identify and characterise the Aspergillus section Flavi isolated from imported peanuts in Malaysia. The internal transcribed spacer (ITS) and β-tubulin sequences were used to confirm the species and determine the phylogenetic relationship among the isolates, while aflatoxin biosynthesis genes (aflR, aflP (omtA), aflD (nor-1), aflM (ver-1), and pksA) were targeted in a multiplex PCR to determine the toxigenic potential. A total of 76 and one isolates were confirmed as A. flavus and A. tamarii, respectively. The Maximum Likelihood (ML) phylogenetic tree resolved the species into two different clades in which all A. flavus (both aflatoxigenic and non-aflatoxigenic) were grouped in the same clade and A. tamarii was grouped in a different clade. The aflatoxin biosynthesis genes were detected in all aflatoxigenic A. flavus while the non-aflatoxigenic A. flavus failed to amplify at least one of the genes. The results indicated that both aflatoxigenic and non-aflatoxigenic A. flavus could survive in imported peanuts and, thus, appropriate storage conditions preferably with low temperature should be considered to avoid the re-emergence of aflatoxigenic A. flavus and the subsequent aflatoxin production in peanuts during storage.